Effects of Collagen Grafting on Cell Behaviors in BCP Scaffold with Interconnected Pore Structure. Issue 1 (December 2016) - Yang, Dong-Jun; Jeon, Jae-Hui; Lee, Sun-Young; An, Hyun-Wook; Park, Keun; Park, Kwang-Bum; Kim, Sukyoung
Abstract Background This study was to investigate the effect of collagen grafted porous biphasic calcium phosphate (BCP) on cell attachment, proliferation, and differentiation. Porous BCP scaffolds with interconnected micropore structure were prepared with were prepared and then grafted with a collagen type I. The hydroxyapatite (HA) and β-tricalcium phosphate (TCP) ratio of the TCP scaffolds was about 60/40 and the collagen was crosslinked on the TCP scaffold surface (collagen-TCP). Results The sintered BCP scaffolds showed fully interconnected micropore structures with submicron-sized grains. The collagen crosslinking in the scaffolds was conducted using the the N-(3-Dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide (NHS) crosslinking method. The cell proliferation of collagen-BCP scaffolds showed a similar result to that of the BCP scaffolds. However, osteoblastic differentiation and cell attachment increased in the collagen-BCP scaffolds. Conclusions Collagen-BCP scaffold improved the cell attachment ability in early phase and osteoblastic differentiation.